Drugs prescribed for patients hospitalized in a geriatric oncology unit: Potentially inappropriate medications and impact of a clinical pharmacist. Issue 6 (November 2016) - Deliens, Coralie; Deliens, Gaétane; Filleul, Olivier; Pepersack, Thierry; Awada, Ahmad; Piccart, Martine; Praet, Jean-Philippe; Lago, Lissandra Dal
Abstract: Objectives: The aim of this study was to assess the prevalence of potentially inappropriate medication (PIM) use upon admission and at discharge in a geriatric oncology unit after involving a clinical pharmacist. Although the few studies conducted in geriatric oncology units used the 2003 Beers criteria, this study used START and STOPP criteria, a more appropriate tool for European formularies. Materials and Methods: Prospective study in older (≥ 70 years) patients consecutively admitted to a geriatric oncology unit in a cancer center from July 2011 to April 2012. Clinical pharmacist conducted a complete comprehensive medication review including non-prescription and complementary (herbals) medications. This information coupled with the patient's medical history allows identifying PIMs using the STOPP and START criteria. The number of PIMs at admission and at discharge from the hospital was compared after clinical pharmacist intervention. Results: Ninety-one older patients with cancer (mean age ± SD = 79 ± 6 years) were included in the study. START criteria identified 41 PIMs for 31 persons (34%) at admission compared to 7 PIMs for 6 persons (7%) at discharge. STOPP criteria identified 50 PIMs at admission for 29 persons (32%) compared to 16 PIMs at discharge for 14 persons (16%). Results showed significantly lower START scores at discharge than at admission (p < 0.001); similarly, STOPP criteria demonstrated fewer PIMs at discharge than at admission (p < 0.001). Conclusion: The use of START and STOPP criteria by a clinical pharmacist allows identifying PIMs and changing prescriptions for older patients with cancer in agreement with the oncologist and geriatrician of the team.